ANALISIS STRUKTUR BIAYA PRODUKSI DAN UNIT COST UNTUK PENGENDALIAN BIAYA PRODUKSI - Mahagiyani Mahagiyani (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
The high number of Usaha Kecil Menengah (UKM), Low-Middle Business, leads to increase tough competition among them. This competition requires the businessmen to improve efficiency and effectiveness inrunning the business. The purpose of this research is to find out the comparison between production cost structure and unit cost or cost per unit. This research is also aimed at controlling production cost through cost structure analysis, cost control and unit cost control. This is based on production cost accounting which consists of raw material cost, manpower cost, and factory overhead cost. In recording the raw material based on the result of the research. It is necessary to use counting method by applying stock card either FIFO or LIFO. In terms of manpower, cost controlling, which has never been done so far, is in need to do so. This card functions to monitor the arrival and leaving time of the workers. Depreciation cost has not been included in overhead cost, such as supporting material cost, electricity and rental. The utilization time of production equipment will be implemented to calculate the overhead cost of production basic expense (cost). Keywords: Production Cost, Cost Component, Production Basic Expenses (Cost), Unit Cost.